International gas contracts - Ason, A (Oxford Institute for Energy Studies, 2022)
This paper offers an overview and explanation of international gas contracts, of which there are several types along the value chain. The key objective of this paper is to focus on two specific categories of long-term agreements for gas and liquefied natural gas (LNG) sales, namely Gas Supply Agreements for pipeline gas (GSAs) and Sale and Purchase Agreements for LNG (LNG SPAs). These two types of long-term supply contracts play a central role in the international gas industry, where natural gas is transported by cross-border pipelines or shipped over long distances in the form of LNG. GSAs and LNG SPAs have a long history. They have underpinned early gas and LNG export projects dating back to the mid-1900s and later drove the development of international gas and LNG trade. Despite the emergence, and growing role, of spot and shorter-term alternatives, long-term GSAs and LNG SPAs have remained the key contractual instruments for international gas and LNG sales. GSAs and LNG SPAs have evolved over time. The early contracts were inflexible arrangements concluded between buyers and sellers for periods often exceeding 20 years, delivering gas and LNG in a rigid (mainly point-to-point) trading model. These contracts offered limited options to modify the rights and obligations of the parties during the lifetime of the contract. At the time parties accepted the rigid contract structures as buyers were seeking security of gas supply and sellers security of offtake. In response to various structural changes in gas markets (including principally market liberalization in North America and Europe), and changing supply and demand fundamentals, gas supply contracts have become increasingly flexible. The general trend towards more flexibility has been reflected in changes to both price and non-price terms in GSAs and LNG SPAs. A greater diversity of pricing mechanisms (including oil-, hub-, spot-indexed and other, price formulas applied on a stand-alone or hybrid basis), volume adjustments for operational purposes, and diversions of LNG cargoes, are some examples of flexible terms that are commonly found in the newer contracts. Notably, the historical principle of risk allocation, where the seller assumes the price risk, and the buyer assumes the volume risk, has remained relevant in long-term contract negotiations. There are no universally accepted general terms for pipeline gas and LNG supply contracts. GSAs and LNG SPAs are negotiated on a case-specific basis. They are typically strictly confidential and combine (1) the commercial choices of the parties and (2) their shared long-term outlook for market changes. In practice, long-term gas and LNG contracts commonly include price review clauses, but, they rarely provide a practicable renegotiation basis for more comprehensive changes to contract terms. The issue of contract reopener mechanisms became particularly relevant during the Covid-19 pandemic, where market circumstances significantly affected performance under gas and LNG contracts and triggered the need for various operational adjustments. More recently, the ability of the parties to renegotiate contract terms has become even more urgent amidst the global search for additional gas and LNG supplies in response to the Russian invasion of Ukraine and related disruptions (executed and anticipated) to Russian gas and LNG exports. The ongoing assessment of the impact of the war in Ukraine arguably presents itself as the most critical and immediate challenge for long-term gas and LNG supply contracts. The continued pursuit of innovation in GSAs and LNG SPAs, along with the emerging contractual responses to decarbonisation requirements, are other examples of the key factors that will shape the outlook for international gas contracts in the future